If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-1) + -7y = -8 Multiply 4 * -1 -4 + -7y = -8 Solving -4 + -7y = -8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -7y = -8 + 4 Combine like terms: -4 + 4 = 0 0 + -7y = -8 + 4 -7y = -8 + 4 Combine like terms: -8 + 4 = -4 -7y = -4 Divide each side by '-7'. y = 0.5714285714 Simplifying y = 0.5714285714
| (x+2)ft= | | c+3+5=c+8 | | 486*2= | | 5x+9=s-23 | | 9z^2+12z-4= | | 4(5x-2)+8=14 | | 0+2+x(x)=38 | | 9(1.35)-2y=13 | | 7m^2+46m=-24 | | N-2.7=5.6 | | 3(-r-1)=4 | | z^2-14x=-40 | | 30=a+(2a+3)+(a+7) | | 3(2x+5)=4x+9 | | (24x-2)=(25x-8) | | 3(2x+5)=4x+8 | | 8x^2+13=213 | | X^4=.25 | | 140-x+40=180 | | 4(s+1.6)=-3s-1.2 | | 2(m-1)=3 | | 9a^2-6a+24=0 | | -3(4x-5)=-10 | | 80=10x+(x-1) | | 5xc=570 | | X+x*3= | | 7a-3=3A | | -23/-17 | | 197+2h=977 | | 2x+6x-9+4=3x-9+3 | | (5x-1)=(3x+1) | | -2a=3-a |